Enhanced external counterpulsation improves dysfunction of forearm muscle caused by radial artery occlusion - Wang, Zhenyu; Yao, Chun; Huang, Lihan; Liang, Jianwen; Zhang, Xiaocong; Shi, Jian; Wei, Wenbin; Zhou, Jing; Zhang, Yahui; Wu, Guifu (Frontiers in Cardiovascular Medicine, 2023)
Objective: This study aimed to investigate the therapeutic effect of enhanced external counterpulsation (EECP) on radial artery occlusion (RAO) through the oscillatory shear (OS) and pulsatile shear (PS) models of HUVECs and RAO dog models. Methods: We used high-throughput sequencing data GSE92506 in GEO database to conduct time-series analysis of functional molecules on OS intervened HUVECs, and then compared the different molecules and their functions between PS and OS. Additionally, we studied the effect of EECP on the radial artery hemodynamics in Labrador dogs through multi-channel physiological monitor. Finally, we studied the therapeutic effect of EECP on RAO at the histological level through Hematoxylin-Eosin staining, Masson staining, ATPase staining and immunofluorescence in nine Labrador dogs. Results: With the extension of OS intervention, the cell cycle decreased, blood vessel endothelial cell proliferation and angiogenesis responses of human umbilical vein endothelial cells (HUVECs) were down-regulated. By contrast, the inflammation and oxidative stress responses and the related pathways of anaerobic metabolism of HUVECs were up-regulated. Additionally, we found that compared with OS, PS can significantly up-regulate muscle synthesis, angiogenesis, and NO production related molecules. Meanwhile, PS can significantly down-regulate inflammation and oxidative stress related molecules. The invasive arterial pressure monitoring showed that 30 Kpa EECP treatment could significantly increase the radial artery peak pressure (p=0.030, 95%CI, 7.236 to 82.524). Masson staining showed that RAO significantly increased muscle interstitial fibrosis (p=0.002, 95%CI, 0.748 to 2.128), and EECP treatment can reduce this change (p=0.011, 95%CI, -1.676 to -0.296). ATPase staining showed that RAO significantly increased the area of type II muscle fibers (p=0.004, 95%CI, 7.181 to 25.326), and EECP treatment could reduce this change (p=0.001, 95%CI, -29.213 to -11.069). In addition, immunofluorescence showed that EECP increased angiogenesis in muscle tissue (p=0.035, 95%CI, 0.024 to 0.528). Conclusion: EECP improves interstitial fibrosis and hypoxia, and increases angiogenesis of muscle tissue around radial artery induced by RAO.